Performance, characteristics, and error rates of cursor control devices for aircraft cockpit interaction. Issue 109 (January 2018) - Thomas, Peter R.
Highlights: Cursor control performance with a standard hands-on-throttle-and-stick fingerstick is significantly weak compared to other potential cockpit control devices but offers support for vibration-induced tremor. Significantly difference throughput groupings are found between joysticks, tracking devices, and touch devices. Trackballs perform better than trackpads at smaller target separation, whilst the reverse is true for larger target separation. Abstract: This paper provides a comparative performance analysis of a hands-on-throttle-and-stick (HOTAS) cursor control device (CCD) with other suitable CCDs for an aircraft cockpit: an isotonic thumbstick, a trackpad, a trackball, and touchscreen input. The performance and characteristics of these five CCDs were investigated in terms of throughput, movement accuracy, and error rate using the ISO 9241-9 standard task. Results show statistically significant differences ( p < 0.001) between three groupings of the devices, with the HOTAS having the lowest throughput (0.7 bits/s) and the touchscreen the highest (3.7 bits/s). Errors for all devices were shown to increase with decreasing target size ( p < 0.001) and, to a lesser effect, increasing target distance ( p < 0.01). The trackpad was found to be the most accurate of the five devices, being significantly better than the HOTAS fingerstick and touchscreen ( p < 0.05) with the touchscreen performing poorly on selecting smaller targets ( p < 0.05). These results would be useful to cockpit human-machine interface designers and provides evidence of the need to move away from, or significantly augment the capabilities of, this type of HOTAS CCD in order to improve pilot task throughput in increasingly data-rich cockpits.